Antimicrobial Activity against Beneficial Microorganisms and Chemical Composition of Essential Oil of Mentha suaveolens ssp. insularis Grown in Sardinia. Issue 3 (7th February 2014) - Petretto, Giacomo Luigi; Fancello, Francesco; Zara, Severino; Foddai, Marzia; Mangia, Nicoletta P.; Sanna, Maria Lina; Omer, Elasyed A.; Menghini, Luigi; Chessa, Mario; Pintore, Giorgio
Abstract The aim of this work was to determine the chemical constituents and in vitro antimicrobial activity of the essential oil (EO) of the aerial parts of Mentha sueveolens spp. insularis grown in Sardinia (Italy) against probiotic and starter microorganisms. The gas chromatography‐mass spectrometry (GC‐MS) analysis allowed to identified 34 compounds, most of oxygenated monoterpene compounds (82.5%) and among them, pulegone was found as major compound (46.5%). The agar diffusion test carried out employing the EO of Mentha suaveolens spp. insularis showed a low antibacterial activity, in particular no action was noticed for probiotic bacteria belonging to lactic acid bacteria groups, whereas almost all yeasts strains tested were inhibited. The automated microtitter dilution assay showed a clear effect at increasing concentration of EO on the specific growth rate (μ) and extension of the lag phase (λ) only for S. xylosus SA23 among bacteria and for Saccharomyces cerevisiae, Tetrapisispora phaffii CBS 4417, Metschnikowia pulcherrima, and Candida zemplinina among yeasts. Results obtained in this work allow us to broaden the knowledge on the effect of EOs on probiotic and food‐related microorganisms. Practical Application Mentha suaveolens spp. insularis may be used in combination with probiotic bacteria into the food matrix or encapsulated in coating and edible films for food preservation.